1552 Improving Control of the Oxygen Saturation During Resuscitation of Preterm Infants with the use of Trend Monitoring. (October 2012) - Goos, T; Rook, D; Eijk, AC van der; Kroon, AA; Dankelman, J; Reiss, IKM
Abstract : Background: The European Resuscitation Council (ERC) guidelines prescribe oxygen saturation (SpO2 ) targets for the first 10 minutes of resuscitation after birth. Unfortunately, the control of SpO2 in newborn infants is difficult. Objectives: To determine whether a device that displays trend lines, reduced deviation from SpO2 targets during resuscitation of very preterm infants after birth. Methods: In a single-centre study, deviation from the SpO2 targets during resuscitation of preterm infants (gestational age (GA) ≤30 weeks) with the aid of a newly developed graphical interface, displaying the trends of SpO2, fraction of inspired oxygen (FiO2 ), was compared with current clinical practice. Data presented as median (IQR). Results: Ten infants (GA 27 4 /7 (25–28 3 /7 ) weeks, birth weight (BW) 812g (694–1068g)) were resuscitated using the graphical interface and 42 infants (GA 27 5 /7 (25 6 /7 –29 1 /7 ) weeks, BW 930g (760–1148g)) were included in the control group. We found that infants resuscitated with the graphical interface spend less time above the SpO2 targets (18% (4–24%) vs. 26% (13–42%)), and had a smaller deviation during the time spend above the SpO2 targets (2.3%SpO2 (1.2–3.8%SpO2 ) vs. 3.8%SpO2 (2.5–6.3%SpO2 )). Both time spend below the SpO2 targets (29% (21–39%) vs. 24% (14–34%)), and deviation below the target (10.5%SpO2 (8.3–25.9%SpO2 ) vs. 7.1%SpO2 (1.9–11.7%SpO2 )) increased. Conclusion: The use of a graphical interface decreased high SpO2 levels during the resuscitation of preterm infants. However, both time spend and deviation below the SpO2 targets increased. It appears the current ERC guidelines are interpreted as the maximum acceptable SpO2, a target range would clarify the acceptable deviation.